Cerebral Circulation and Metabolism of Patients with Cerebral Injury - Ekaterina A. Abramova; Oleg V. Voennov; Gennadii A. Boyarinov; Аlexei O. Trofimov (Общая реаниматология, 2018)
The purpose of the study was to asses changes in cerebral macrocirculation and metabolism parameters in patients with concomitant cerebral injury during infusions of ethylmethylhydroxypyridine succinate at a dose of 12.5 to 100 mg/h depending on a source pattern of the cerebral blood flow.Materials and methods. The study included 25 patients with severe concomitant cerebral injury who administered ethylmethylhydroxypyridine succinate (EMHPS) intravenously in addition to the standard therapy at a dose of 12.5 mg/h for 1 hour, then the dose was increased up to 25 mg/h within 1 hour, then up to 50 mg/h within 1 hour followed by an infusion at a dose of 100 mg/h for 1 hour. Cerebral macrocirculation parameters were analyzed every hour before each dose increase. Transcranial dopplerography (TDG) was used to assess the following linear blood flow velocity (LBFV) parameters: systolic (Vmax), diastolic (Vmin), medium (Vm) LBFV, pulsation index (PI) and resistance index (RI), as well as glucose and lactate levels, lactate dehydrogenase (LDH) activity and the pH level in venous blood from a jugular vein.Results. Positive changes of LBFV parameters in the form of cerebral perfusion increase were recorded in patients with hindered perfusion and hypoperfusion patterns after EMHPS infusions at a dose of 12.5 to 100 mg/h. Patients with a mild vasospasm pattern presented favorable changes in LBFV parameters including a decrease in velocity parameters, normalization of the pulsation index and the resistance index which confirmed normalization of the vascular tone and vasospasm elimination. Positive changes in LBFV parameters in patients with a hyperperfusion pattern were noticed in the form of the reduction of hyperemia manifestations and normalization of the vascular tone. Patients with a severe vasospasm pattern presented normalization of the vascular tone. Normalization of LBFV parameters was accompanied by normalization of the lactate level, lactate dehydrogenase activity and the pH level in venous blood. Optimal values were found in infusions at a dose of 50—100 mg/h.Conclusion. Infusions of EMHPS at a dose of 12.5—100 mg/h to patients with concomitant cerebral trauma resulted in normalization of LBFV and metabolism parameters in patients with all kinds of CBF patterns.